2018
DOI: 10.3390/en11071832
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Solar Energy Usage for Dwelling Heating, Using Solar Collectors and Medium Sized Vacuum Insulated Storage Tank

Abstract: This article describes a method for increasing the solar heat energy share in the heating of a dwelling. Solar irradiation is high in summer, in early autumn, and in spring, but during that same time, the heat demand of dwellings is low. This article describes a solution for storing solar heat energy in summertime as well as the calculations of the heat energy balance of such a storage system. The solar heat energy is stored in a thermally insulated water tank and used in the heating period. The heat is also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Then the loop system for residential users provides directly heat or pump system further heating lower temperature solar heat transform the energy to the residents to use again. One study has concluded that through 15 m 3 storage tank can provide 41% of the solar direct heating demand for homes and direct heating system efficiency is 51% under its relevant system [24]. In addition, through SWH (Solar water heating) system simulating the household domestic hot water demand, the study changes the solar energy collector area, storage tank volume and other components to optimize heating circulation system and collector parameters so as to adjust the solar energy reception rate in the best circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…Then the loop system for residential users provides directly heat or pump system further heating lower temperature solar heat transform the energy to the residents to use again. One study has concluded that through 15 m 3 storage tank can provide 41% of the solar direct heating demand for homes and direct heating system efficiency is 51% under its relevant system [24]. In addition, through SWH (Solar water heating) system simulating the household domestic hot water demand, the study changes the solar energy collector area, storage tank volume and other components to optimize heating circulation system and collector parameters so as to adjust the solar energy reception rate in the best circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing self-consumption stabilises load peaks and decreases costs on the electrical energy purchase [14]. Other research studies with a similar objective as this study, but based on solar PV, are described in the references [11,12], while cross-seasonal storage is discussed in others [15,16]. The latter demonstrates the possibility of increasing self-consumption by incorporating space heating demand and using large volumes of water and concrete to store energy.…”
Section: Overview Of Literaturementioning
confidence: 72%
“…Solar-combi systems constitute a popular subject in the relevant scientific literature. They are usually introduced and investigated for indoor space heating for residential buildings [21][22][23][24][25], while studies have been also executed for school buildings [26], hotels [27], swimming pools heating [28,29], even for central heating district systems [30] and advanced systems for both pure and hot water production [31]. The relevant research has been concentrated on:…”
Section: Solar-combi Systemsmentioning
confidence: 99%